Comparison of The Effectiveness of Dexamethasone and Ondansetron In Preventing Postoperative Nausea and Vomiting (PONV) In Elective Surgical Patients: A Systematic Review - Chiristian Rein Sihombing (Riviera Publishing, 2025)
Postoperative nausea and vomiting (PONV) is one of the most common postoperative complications and may reduce patient comfort, prolong hospital stay, and lead to further complications. Ondansetron and dexamethasone are widely used antiemetic agents for PONV prophylaxis; however, the comparative effectiveness of both drugs as monotherapy remains inconsistent across studies. This systematic review aimed to compare the effect of dexamethasone versus ondansetron on the incidence of PONV in patients undergoing elective surgery. This study was conducted according to the PRISMA 2020 guidelines. Literature was searched through multiple electronic databases. Eligible studies were randomized or quasi-randomized controlled trials involving adult patients undergoing elective surgery who received dexamethasone or ondansetron as PONV prophylaxis. Study selection was performed systematically, and five studies met the inclusion criteria for qualitative analysis. The findings demonstrated that dexamethasone and ondansetron showed relatively comparable effectiveness as monotherapy in reducing the incidence of PONV within the first 24 hours after surgery. However, several studies indicated that the combination of dexamethasone and ondansetron provided superior antiemetic efficacy compared with monotherapy. Dexamethasone and ondansetron are equally effective as monotherapy for PONV prophylaxis in elective surgical patients. In patients at high risk of PONV, the combination of both agents is more strongly recommended.